Clinical, radiological, and molecular diagnosis of progressive fibrodysplasia ossificans - Vianey Ordóñez-Labastida; Alan Cárdenas-Conejo; Juan C. Huicochea-Montiel; Guadalupe E. Paredez-Rivera; Alberto Hidalgo-Bravo; Lucero M.J. Monterde-Cruz; María A. Aráujo-Solís (Permanyer, 2021)
Background: Progressive fibrodysplasia ossificans is a rare genetic disease with heterozygous mutations (autosomal dominant inheritance) in the ACVR1 gene, which causes progressive heterotopic ossification in muscles, tendons, and ligaments, usually secondary to trauma. The ossification foci generate pain, joint ankyloses, and restricted movement. Congenital shortening and medial deviation first metatarsal of the foot is a distinctive feature. This report aimed to present an educational value case of a patient with clinical, imaging, and molecular diagnosis of progressive fibrodysplasia ossificans, recognized as a rare condition that severely affects the quality of life. Case report: We present the case of a 6-year-old female patient with lumps in the right scapular and dorsal region, progressive joint rigidity, and short first metatarsal medially deviated since birth. By imaging studies, we established the diagnosis of progressive fibrodysplasia ossificans. Sanger sequencing of ACVR1 reported c.617G>A (p.Arg206His). Conclusions: Confirmation of the diagnosis allowed genetic counseling, including a comprehensive explanation of the disease's natural history and measures to prevent its rapid progression.